The STUDY OF RESISTANT EARTHHQUAKE BUILDING OF TIMBER ROOFS STRUCTURE AND ITS RETROFIT AND REDESIGN AFTER THE SEPTEMBER 28 2018 EARTHQUAKE - Ketut Sulendra (Jurnal Sains dan Teknologi Tadulako, 2023)
Palu’s Earthquake on 28 September 2018 had caused structural failure including buildings with wooden structures which were knew as an earthquake-resistant structures. This study will discuss existing building timber roofs structure were damaged after the earthquake, various and caused of the damaged. Existing and retrofitted timber rooss and alternatives design of the roofs structures will be compared. Retroffited timber roof, truss roof with 70x70x6 double angle and gable frame roof structure with WF 250x125 will be design with 15 m length span and 45° slope. Based on these data collected from initial assessment of that buildings, analysis was conducted. Detailed assessments were carried out, when analysis of the truss, frame and joint of roofs structures were needed. Results of the initial assessment of wooden structure, showed that damages occurred at the many joints of member joints and joint-connection between wall and truss as the poor connection system. Redesign showed were structural behavior of retrofitted timber roof, double angle truss roof and gable frame roof structure showed better strength, stiffness and ratio of member force to self-weight.